2017
DOI: 10.1002/ejlt.201600366
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism and prospects for targeted therapy of cancer

Abstract: Fatty acids are fundamental substrates required for energy storage, synthesis of membranes, generation of signaling molecules and lipid droplet formation in cancer cells. High levels of fatty acid metabolic activity are one of the most aberrant metabolic alterations in cancer cells. The de novo fatty acid synthesis pathway is the primary source of fatty acids in cancer cells, but cancer cells can also acquire fatty acids through the lipolytic pathway, which helps cells survive and maintain their invasiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Overall, the FA ion intensities demonstrated an increasing trend from muscle to epithelium to cancer tissue in ESCC. It has been reported that cancer cells rapidly produce FAs to meet the urgent need for membrane biosynthesis, cellular signaling, and energy consumption (3, 39). In the FA biosynthesis pathway, FASN is a key metabolic enzyme for the de novo synthesis of FAs.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the FA ion intensities demonstrated an increasing trend from muscle to epithelium to cancer tissue in ESCC. It has been reported that cancer cells rapidly produce FAs to meet the urgent need for membrane biosynthesis, cellular signaling, and energy consumption (3, 39). In the FA biosynthesis pathway, FASN is a key metabolic enzyme for the de novo synthesis of FAs.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported by other groups that the increasing amount of saturated fatty acids within the liver provokes endoplasmic reticulum stress, apoptosis, and liver injury [14,15]. Therefore, nowadays, fatty acid metabolic pathways are often considered as a target for anticancer therapy [16,17]. Moreover, alteration of polyunsaturated fatty acid levels and the signaling pathways that they regulate also was detected in various neurological disorders (e.g., Alzheimer’s disease and major depression) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids (FAs) are critical endogenous molecules for cellular energy storage, membrane formation, and signal transmission. It has been reported that upregulation of fatty acid synthesis is one of the most aberrant metabolic features of tumors and is required for membrane proliferation, energy consumption, lipid droplet formation, and signaling generation in various cancers ( Chen and Li, 2017 ). The ion intensities of several FAs were found to be an increasing trend from the muscle to the epithelium to cancer tissue in ESCC, which was in good agreement with the expression of FASN, a critical metabolic enzyme for the de novo synthesis of FAs ( Sun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%